Luther's body language: Re‐membering the reformer1. Issue 3 (2nd September 2018) - Stortz, Martha E.
Abstract: Martin Luther's Reformation is too often taken as a head trip, and theologians analyze the reformer's theology by looking at the great doctrines he launched, like the doctrine of justification by grace through faith, and the Reformation  solas— by faith alone,   sola fide ; by grace alone,   sola gratia ; by scripture alone,   sola scriptura;  and Christ alone,   solus Christus .   But theology comes out of hands‐on experience, and Luther's is no exception. Each of those great doctrines was attached to concrete situations and actual bodies in motion. I look at Luther's theology in the context of three bodies, his experience with his own body, with the body of Christ, and with the body politic. Then, I pose to Luther's body language a very Lutheran question: "What does this mean?" For us. Today.